2016
DOI: 10.1155/2016/2830394
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Eight Domestic Goat Populations Raised in Turkey

Abstract: The objective of this study was to determine the intra- and intergenetic diversities of eight different goat populations in Turkey including Hair, Angora, Kilis, Yayladag, Shami, Honamli, Saanen, and Alpine. A total of 244 DNA samples were genotyped using 11 microsatellites loci. The genetic differentiation between breeds was considerable as a result of the statistically significant (P < 0.001) pairwise F ST values of each pair of breeds. Exceptionally, F ST values calculated for Honamli and Hair breeds were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 22 publications
7
14
9
Order By: Relevance
“…A neighbor‐joining network used to analyze 16 goat populations in the littoral zone of the Yangtze River revealed that most populations were clustered together based on their geography, such as the two Qinghai populations (QH and CM) and the Hubei populations (EB and YC), which grouped together into Cluster II and Cluster VII, respectively. These results were consistent with many previous reports regarding the different population relationships among goats (Bulut et al., ). However, Cluster I and Cluster IV consisted of different ecogeographic populations, which indicated that the gene flow and migration among populations occurred with a high frequency in the Chongqing, Sichuan, and Yunnan goat populations.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A neighbor‐joining network used to analyze 16 goat populations in the littoral zone of the Yangtze River revealed that most populations were clustered together based on their geography, such as the two Qinghai populations (QH and CM) and the Hubei populations (EB and YC), which grouped together into Cluster II and Cluster VII, respectively. These results were consistent with many previous reports regarding the different population relationships among goats (Bulut et al., ). However, Cluster I and Cluster IV consisted of different ecogeographic populations, which indicated that the gene flow and migration among populations occurred with a high frequency in the Chongqing, Sichuan, and Yunnan goat populations.…”
Section: Discussionsupporting
confidence: 94%
“…To date, the global diversity of local goats has been assessed using various molecular tools, and such studies have been conducted in Spain (Ferrando et al., ; Manunza et al., ), Africa (Awotunde et al., ; Kibegwa, Githui, Jung'a, Badamana, & Nyamu, ; Mdladla, Dzomba, Huson, & Muchadeyi, ), the Americas (Carvalho, Paiva, Araújo, Mariante, & Blackburn, ), Europe (Bulut, Kurar, Ozsensoy, Altunok, & Nizamlioglu, ; Windig et al., ), and Asia (Lin et al., ; Nicoloso et al., ; Waki, Sasazaki, Kobayashi, & Mannen, ; Yadav, Gahlot, Gahlot, Asraf, & Yadav, ).…”
Section: Introductionmentioning
confidence: 99%
“…The allelic diversity in Sri Lankan goats was found to be in a similar range as reported for South East Asian [Malaysia (Marini et al, 2014); Thailand (Anothaisinthawee et al, 2012)] and South Asian goats [Pakistan (Vahidi et al, 2014); Bangladesh (Afroz et al, 2010)]. However, higher allelic diversity was reported in Indian (Rout et al, 2008), Iranian (Vahidi et al, 2014), Turkish (Bulut et al, 2016), Saudi Arabian (Canon et al, 2006), Nigerian (Murital et al, 2015), North African (Elbeltagy et al, 2016) and European (Canon et al, 2006) goats. Allelic diversity in Korean goats (Kim et al, 2002) was observed to be much lower than Sri Lankan goats.…”
Section: Genetic Variability and Test For Hardy-weinberg Equilibriumsupporting
confidence: 68%
“…Nevertheless, high H O values (i.e., 0.880 < H O < 0.980) are also reported in the literature for other goat breeds at different microsatellite loci (Araújo et al, 2006;Oliveira et al, 2010;Bulut et al, 2016). The mean values of observed and expected heterozygosities in the breeds analyzed were high (≥0.696; Table 4), suggesting a high genetic variability.…”
Section: Discussionsupporting
confidence: 55%